ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INDEKS HARGA SAHAM GABUNGAN DI BURSA EFEK INDONESIA PERIODE - Purwaningsih, Dwi; Sulistiyani, Tina (Jurnal Fokus Manajemen Bisnis, 2015)
This study aims to determine the effect of the money supply, inflation, and SBI interest rates partially and simultaneously on the composite stock price index on the Indonesia Stock Exchange (BEI) in 2012-2014, the type of data and data sources used in this study are data secondary data from the Bank Indonesia Annual Report, the Indonesian Ministry of Trade Institute, and Exchange Corner Financial Data. To analyze the data of this study used a multiple linear regression analysis tool that aims to determine the effect of the money supply, inflation, and SBI interest rates on the Composite Stock Price Index using SPSS statistical tools. Based on this research, the research method used in the first hypothesis is the Statistical t test and the second is the Statistical F test. Based on the results of this study indicate that the variable Money Supply has a significant effect on the Composite Stock Price Index. For the inflation variable does not have a significant effect on the Composite Stock Price Index. And the SBI Interest Rate variable has a significant effect on the Composite Stock Price Index. Together these three independent variables (Amount of Money Supply, Inflation, SBI Interest Rates) have a significant influence on the dependent variable (Composite Stock Price Index).